2016
DOI: 10.1039/c6ra09217a
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of hydrogen peroxide on the oxidase-like activity of nanoceria and its application for colorimetric hydrogen peroxide and glucose sensing

Abstract: Nanoceria (cerium oxide nanoparticles) exhibits excellent catalytic activity towards chromogenic substrate 3,3,5,5-tetramethylbenzidine (TMB) in the presence of hydrogen peroxide (H 2 O 2 ), which has been reported. However, the understanding on the interaction between H 2 O 2 and nanoceria is far from complete. Herein, we further studied the interaction between H 2 O 2 and dextran-coated nanoceria and found that H 2 O 2 plays a dual role on nanoceria's oxidase activity both as an inhibitor and a promoter, dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…Nanoceria becomes an ideal and impacted biosensor, not only because it can provide immediate and real time measurement of biomolecules [32,33], but also because it can have many advantages over organic biosensor, such as photo bleachable, toxic, expensive, and easily degradable. Nanoceria has already become a hot topic in biosensor fields.…”
Section: 2mentioning
confidence: 99%
“…Nanoceria becomes an ideal and impacted biosensor, not only because it can provide immediate and real time measurement of biomolecules [32,33], but also because it can have many advantages over organic biosensor, such as photo bleachable, toxic, expensive, and easily degradable. Nanoceria has already become a hot topic in biosensor fields.…”
Section: 2mentioning
confidence: 99%
“…The utilization of nanoceria as oxidase under some special circumstances was also reported. Recently, nanoceria have been used for several applications either in biotic conditions or abiotic conditions, such as antioxidants, [63][64][65] capping [36] and neuroprotection agents, [66][67][68][69][70][71][72] biosensors, [23,28,73] immunoassays, [31,32,74] color indicator [27,[75][76][77][78][79] and so on.…”
Section: Bio-application Prospects Of Nanoceria As Enzyme Mimeticsmentioning
confidence: 99%
“…The negatively charged target DNA could not only be adsorbed on the surface of nanoceria with positive charge, but also be adsorbed on positively charged 3,3',5,5'-tetramethylbenzidine (TMB), blocking the direct contaction of nanoceria with TMB and resulting in a lower colorimetric signal. Furthermore, Guo et al [78] studied the interaction between H 2 O 2 and nanoceria for the TMB colorimetric determination was dependent on the H 2 O 2 concentration. The results showed that the oxidase mimetic activity of nanoceria would be promoted when the H 2 O 2 concentration was above millimolar level, while under this level the catalysis activity was inhibited.…”
Section: Immunoassaysmentioning
confidence: 99%
“…In this study, diluted hydrogen peroxide between 2% and 10% by volume is flushed into the non-contact megasonic cleaner to facilitate the removal of ceria abrasive particles. 16 In the current study, the concentration of H 2 O 2 in the megasonic tank is on the order of 1.0 M (between 10% and 2% by vol.). Consequently, the oxidation of Ce 3+ to Ce 4+ should be the main mechanism involved.…”
Section: 12mentioning
confidence: 65%